If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12m + 6 = 4m + 2 Reorder the terms: 6 + -12m = 4m + 2 Reorder the terms: 6 + -12m = 2 + 4m Solving 6 + -12m = 2 + 4m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-4m' to each side of the equation. 6 + -12m + -4m = 2 + 4m + -4m Combine like terms: -12m + -4m = -16m 6 + -16m = 2 + 4m + -4m Combine like terms: 4m + -4m = 0 6 + -16m = 2 + 0 6 + -16m = 2 Add '-6' to each side of the equation. 6 + -6 + -16m = 2 + -6 Combine like terms: 6 + -6 = 0 0 + -16m = 2 + -6 -16m = 2 + -6 Combine like terms: 2 + -6 = -4 -16m = -4 Divide each side by '-16'. m = 0.25 Simplifying m = 0.25
| 110+29n= | | 6m+53=m(6+3)+38 | | K-63/3=10 | | Log*10=1 | | x+46=4x+22 | | 3y^2-x^2=9 | | 3(t+17)=6 | | 16.01=3g+3.62 | | (3+4i)+(7-2i)= | | 1.06g-4=0.77 | | x=2lny | | 0=2m^2+9m+4 | | 3y-2/5+2=7 | | 2w^2+w-42=0 | | 19x^2-22= | | (2x-29)=(x+5) | | 69x^4+35x^4+72x^6= | | 6y-2=5u-1 | | 3(2x-1)-3(4-2x)=6 | | 3y/4-4=8 | | (2x-29)+(x+5)=180 | | 8v+2-3v-6= | | 0.8+0.2-5x= | | 16x+112=64+132x+14x | | 8+4(z-2)=-5x+8 | | x+0.2-5x= | | -6(x+2)+15=-4x-7 | | 3.2=4.4-0.3x | | (7x+1)+(13x+9)=90 | | 2(4-3x)-10=2x-74 | | 4x^3-9x^2-2=0 | | 13y-1.8=-5y+3.6 |